Primary health care tasks in implementing the main operations of public health - Tyszko, Piotr Zbigniew; Nitsch-Osuch, Aneta; Mińko, Magdalena; Kanecki, Krzysztof (Family Medicine & Primary Care Review, 2016)
Public health and primary health care are complementary strategies for sustaining the health of a society. There are many analyses in the literature on the subject that deal with the possibility of mutual support between public health and primary health care. There reports from many countries include studies of scientific institutions, presentations of specific solutions used by health protection administrations and self-government bodies, programs of study, and courses. However, this issue is rarely raised in Poland. The aim of this article is to present an up-to-date list of public health operations and to where there is room for primary health care activities. A binding list of public health operations was defined by the World Health Organisation (WHO) in 2012 under the name of Essential Public Health Operations (EPHOs). In order to define public health operations more precisely in this article, a questionnaire self-assessment tool for the evaluation of essential public health operations in the WHO European Region was used. Primary health care plays a significant role in the performance of public health operations (EPHOs), whereas the public health operations connected with health protection (EPHO 3), health promotion (EPHO 4) and disease prevention (EPHO 5), are mostly attributed to primary health care. Primary health care provides the information necessary for the performance of public health operations in the field of monitoring population health and well-being – in particular infectious and chronic diseases (EPHO 1), and for health care management and improvement of health care quality (EPHO 6).